MODERN METHODS FOR ASSESSING THE LEVEL OF COMPETITIVENESS OF ENTERPRISES IN THE SERVICE SPHERE - DRAZHNYTSIA, SERHII; DRAZHNYTSIA, OLEH (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The main trends in the development of service enterprises are the increase of foreign capital, the formation of new economic ties, the integration of the domestic market of services in European and world markets. At the same time, the positive dynamics of development of the domestic market of services is constantly accompanied by unpredictable changes, primarily related to the economic situation in Ukraine. The purpose of this study is to form a modern classification of methods for assessing the competitiveness of service enterprises. To achieve this goal, a range of research tasks was determined, including: 1) study of the essence of the efficiency and competitiveness of the activities of enterprises in the service sector, the order and main criteria for their assessment; 2) characteristics of existing methods for assessing the level of competitiveness of enterprises; 3) the formation of a modern classification of methods for assessing the level of competitiveness of enterprises in the service sector. Having studied different approaches to defining the essence of the efficiency and competitiveness of enterprises, the authors give their generalized definition, which defines the essence of the competitiveness of enterprises as a complex integral characteristic of its effective activity. Therefore, evaluating the efficiency of an enterprise, we also evaluate its competitiveness. Based on the above characteristics of existing methods for assessing the level of competitiveness of service enterprises, the authors propose a modern classification of these methods, which is based on the assertion that assessing the competitiveness of an enterprise is a sequential process that begins with assessing the market and the competitive environment, smoothly moving on to analyzing the position of the enterprise. among competitors, and ending with the evaluation of the product (service) itself.